PEMBAHARUAN LOCA ANTARA BALI FSS DENGAN UNIT JOKOTOLE TERKAIT PENGIRIMAN BERITA PENERBANGAN DI PERUM LPPNPI CABANG DENPASAR - Erdiyawan Tabligh Hidayah; Lusiana Dewi Kusumayati; Yeni Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
In flight information services, good cooperation is needed between each unit, Bali FSS and the Jokotole Aeronautical Station are no exception. The two stations are interrelated in terms of coordination to convey all flight information needed by each station. The coordination has been arranged in a Letter of Operational Coordination Aggrement (LOCA) which must be obeyed by both parties. But in reality the existing LOCA is not in accordance with the conditions in the field, so the author aims to do a review of the LOCA between Bali FSS and the Jokotole Aeronautical Station so that the provision of flight traffic services can run effectively and efficiently. With the LOCA amendment, it is expected to be able to perfect the existing rules so that it strengthens the legal foundation and helps improve the smoothness of aviation information services, especially in the delivery of ATS news at the Denpasar branch of LPPNPI. Qualitative description is a method used to describe facts or data from the influence that will be explained by interviews, literature studies, observations, and documentation as well as direct observations that refer to several sources that are relevant and have credibility. The population of this research is Aeronautical Communication Officer (ACO) personnel at Perum LPPNPI Denpasar Branch, while the authors take several samples from the population, namely ACO personnel at Perum LPPNPI Denpasar Branch The results of this study are the procedure distribution of ATS Messages between Bali FSS with Jokotole Aeronautical Station need to be optimized into LOCA. So as to protect personnel in carrying out their duties and responsibilities as an Aeronautical Communication Officer.